RELATIONSHIP BETWEEN LONG-SUFFERING AND DIABETES DISTRESS WITH DIETARY ADHERENCE AMONG DIABETES MELLITUS PATIENTS: A CROSS-SECTIONAL STUDY - Purwanti, Aisyah Tri; Ratnawati, Leersia Yusi; Rohmawati, Ninna (Journal of Public Health Research and Community Health Development, 2024)
Background: The prevalence of diabetes melitus is increasing significantly. Dietary adherence in people with diabetes mellitus is difficult to achieve because it requires regular long-term changes throughout their lives. It also has an impact on the psychology of people with diabetes mellitus to experience distress. Purpose: Analyze the relationship of long suffering and diabetes distress with dietary adherence in diabetes mellitus patients. Methods: This research uses analytical methods with a cross-sectional design. There were 71 respondents who were taken from 1320 diabetes mellitus patientin Puskesmas Talango by simple random sampling method. Data collection was using the Diabetes Distress Scale and Perceived Dietary Adherence Questionare Questionnaires. chi square was used for bivariate analysis. Results: The results showed that dietary adherence had a significant relationship with diabetes distress (p=0.001) but had no relationship with long-suffering (p=0.100). Conclusion: There is a significant relationship between education, income, and diabetes distress with dietary adherence.